Morphometric Study of Tibia in Kenguri Sheep - Awate, Annapurna (Indian Journal of Veterinary Anatomy, 2020)
A morphometric study was undertaken on tibia of Kenguri sheep. The left and right tibial bones of both sexes were divided into four groups. Group-I included up to 6 months of age, Group-II included above 6 months to 2 years of age, Group-III included above 2 years to 4 years and Group-IV above 4 years to 6 years. The parameters considered were the mean lengths, width and circumference at both extremities, at mid shaft level, and at the level of nutrient foramens of bones. The mean total length of tibia in group-I and group-IV animals was 15.62±1.28cm and 23.75±0.27cm respectively. The mean width at proximal extremity of tibia was 04.43±0.06cm and at distal extremity was 03.27±0.07cm in group-II animals. The mean mid shaft circumference of group-III animals was 04.67±0.07cm. The morphometric parameters of tibia were increased as age advances in the Kenguri sheep, but there was no significant difference (P>0.05) between the left and right tibia of same groups.